LncRNA NEAT1/miR‐495‐3p regulates angiogenesis in burn sepsis through the TGF‐β1 and SMAD signaling pathways. Issue 1 (16th January 2023) - Meng, Yanbin; Hao, Zhenming; Zhang, Hairui; Bai, Peiyi; Guo, Wanli; Tian, Xiaorui; Xu, Jun
Abstract: Introduction: To investigate the role of the long‐chain noncoding RNA (lncRNA) nuclear enriched abundant transcript 1 (NEAT1) in the process of angiogenesis in human umbilical vein endothelial cells (HUVECs) and illustrate its potential role in burn sepsis (BS) pathogenesis. Methods: HUVECs were treated with BS patient serum or healthy control serum. NEAT1 shRNA, miR‐495‐3p mimics, and miR‐495‐3p inhibitor were transfected into HUVECs. NEAT1 and miR‐495‐3 levels in serum or HUVECs were detected using quantitative reverse transcription‐polymerase chain reaction. Cell counting kit‐8 and flow cytometry assays were used to explore the proliferation and apoptosis of HUVECs. The expression of vascular endothelial growth factor (VEGF) in the supernatant was detected using enzyme‐linked immunosorbent assay. Tube formation of HUVECs was also analyzed. Western blot analysis was used to analyze signaling pathway proteins. Results: In HUVECs stimulated with BS patient serum, NEAT1 expression was increased, while miR‐495‐3p expression was decreased. In addition, NEAT1 silencing by specific shRNA inhibited cell proliferation, VEGF production, and tube formation under burn patient serum treatment, which decreased the TGFβ1/SMAD signaling pathway activation. Moreover, miR‐495‐3p minics inhibited angiogenesis and the activation of signaling pathways induced by NEAT1 shRNA. Furthermore, miR‐495‐3p inhobitor promoted angiogenesis in HUVECs and activated the TGFβ1/SMAD signaling pathway. In patients with BS, NEAT1 expression was significantly increased and miR‐495‐3p expression was decreased compared to healthy controls, and NEAT1 and miR‐495‐3p expression was associated with the clinical features of patients. Conclusions: Our results indicate that lncRNA NEAT1 regulates angiogenesis and activates the TGFβ1/SMAD signaling pathway during the occurrence of BS. Abstract : We found that the nuclear enriched abundant transcript 1 (NEAT1) expression promoters angiogenesis in human umbilical vein endothelial cells under burn sepsis (BS) patient serum treatment by regulating miR‐495‐3p and activating the TGF‐β1/SMAD signaling pathway. These observations may provide new insights into the application of NEAT1 for the clinical management of BS patients.